Estudio geológico-ambiental del área de emplazamiento de la planta de tratamiento de aguas residuales de la parroquia Sumaypamba del cantón Saraguro. - Morocho Malla, Edison Rolando (2014)
The present work has as purpose the geologic-environmental study for the future construction of a plant of treatment of residual waters in the sector of Sumaypamba belonging to the canton Saraguro county of Loja, mediating activity which you/they were considered necessary the realization of studies that you/they determined technical specific situations of the place of importance. Geologic mind the sector is located inside the Group Ayancay and it leaves of the Formation Uchucay, he/she is conforming the basin of the River Jerkins main reason for that there is prevalence of sedimentary material, this sector coluvials it is characterized by the presence of very defined stratifications and for the characteristic presence of drying cracks of slime-loamy material, the clay layers present buzament of 45°SE and direction of 9° NE the plegaments near place they are imperceptible. The realization of a test geotechnical (SPT) was made for the considered sector, the results that they were obtained they consider to the land as good to support a concrete structure or another construction material, the results show that the carrying capacity of the floor resists a load of 49 ton/m2 considering half-boots of 1, 1.5 and 2m; therefore the present work contains data and charts that show the characteristics from the most general to the most specific for the construction area. As for the environmental analysis it was considered important to carry out physical-chemical analysis of the bed that gathers the gray waters of the whole sector, the gathered samples and georefenciadas they follow a sampling protocol that after having transported and examined in the laboratory they give the deductions that allow us to know the grade of contamination and this way to understand the necessity to treat this resource, certainly in the deductions of the results the quality of waters you the conceptual like terrible and bad, reason for which needs to be processed before uniting to other bodies of water.